Dietary Change Interventions for Undergraduate Populations: Systematic Review and Recommendations. Issue 1 (2nd January 2017) - Pember, Sarah E.; Knowlden, Adam P.
ABSTRACT: Background : Research demonstrates a decline in healthy eating behaviors during transitional years at university, potentially leading to weight gain and establishing maladaptive dietary habits.Purpose : This systematic review assessed the efficacy of previous nutrition interventions for undergraduates, evaluating design and implementation.Methods : Boolean phrases searched were "nutrition OR healthy eating, " "undergraduate*, " "pilot study OR intervention*, " and "college OR university." Articles were included if they were peer-reviewed, published in the last 10 years, and described complete interventions targeting undergraduates that included dietary behavior change, or the intention for change, as an outcome.Results : Of the 10 programs examined, only 4 showed significant increases in fruit and vegetable consumption, 1 showed an increase in fruit purchase, and 1 resulted in an increase in fruit consumption. The majority of interventions ( n = 7) simultaneously targeted other health behaviors, and only one addressed environmental changes. Methodology was varied and inconsistent.Discussion : Limited success in undergraduate nutrition interventions may be the result of targeting multiple behaviors and a lack of evidence and theory-based design.Translation to Health Education Practice : Theory-based studies exclusively focused on dietary behaviors are needed that address social norms, upperclassmen and nonresidential students, environmental supports, feedback, goal setting, and measures aside from fruit and vegetable consumption.